Residual alcohol use disorder symptoms after treatment predict long‐term drinking outcomes in seniors with DSM‐5 alcohol use disorder. (9th October 2021) - Behrendt, Silke; Kuerbis, Alexis; Braun‐Michl, Barbara; Bilberg, Randi; Bühringer, Gerhard; Bogenschutz, Michael; Mejldal, Anna; Andersen, Kjeld; Søgaard Nielsen, Anette
Abstract: Background: Risk of relapse within the first months after alcohol use disorder (AUD) interventions is substantial among older adults. For this vulnerable group, little information exists on how this risk is associated with residual DSM‐5 AUD symptoms after treatment. Aims: To investigate among older adults who received short‐term treatment for DSM‐5 AUD (1) the prediction of drinking behaviors and quality of life 12 months after treatment initiation by 6‐month DSM‐5 AUD symptoms, AUD severity, and AUD remission, and (2) whether these DSM‐5 AUD indicators provide prognostic information beyond that gained from 6‐month alcohol use (AU) status. Methods: The international multicenter RCT "ELDERLY‐Study" enrolled adults aged 60+ with DSM‐5 AUD. We used data from the subsample of 323 German and Danish participants with complete DSM‐5 AUD criterion information 6 months after treatment initiation (61% male; mean age = 65.5 years). AU was assessed with Form 90, DSM‐5 AUD with the M.I.N.I., and quality of life with the WHOQOL‐BREF. Generalized linear models were applied to investigate the associations between 6‐month AUD indicators and 12‐month AU and quality of life. Results: Independent of AU at 6 months, having 1 (vs. no) residual AUD symptom at 6 months predicted a 12‐month "slip, " defined as exceeding a blood alcohol concentration of 0.05% at least once during that time (OR: 3.7, 95% CI: 1.5 to 9.0), heavy episodic drinking, and hazardous use ( p  < 0.05). AUD remission was associated with a lower risk of a "slip" at 12 months ( p  < 0.05). Failed reduction/cessation was associated with poorer physical health (Coef.: −0.4, 95% CI −0.7 to −0.1). Conclusion: For older adults, residual AUD symptoms in the first months after short‐term treatment predict problematic AU outcomes during the first 12 months after treatment entry. Thus, residual symptoms should be addressed in this patient population during posttreatment screenings. Abstract : In older adults treated for DSM‐5 alcohol use disorder (AUD), we found that having at least one residual AUD symptom at the 6 month follow‐up after treatment predicted a 12 month 'slip' (exceeding a blood alcohol concentration of 0.05% at least once), heavy episodic drinking, and hazardous use (adjusted for 6 month alcohol use). Few significant associations showed between specific residual symptoms at 6 months and alcohol use at 12 months and between residual symptoms and quality of life at 12 months.